The influences of extroversion and introversion on language learning behaviours of ESL learners - Hum, Hui Yun (2022)
This research aims to identify the relationship between personality, extroversion-introversion and learners’ second language learning behaviours. Besides, the preferable second language learning behaviours of extroverted and introverted learners are also intended to be found out through this study. 81 students had been reached out to through purposive sampling. To achieve the research objectives, the researcher used Google Form to distribute three questionnaires: general demographic information, the Eysenck Personality Questionnaire (EPQ), and the Strategy Inventory for Second Language Learning (SILL, version 7.0). The researcher employed instruments, Microsoft Excel and Statistical Package for the Social Sciences (SPSS, version 26) to assist in analysing the statistics. The research project revealed that there is a correlation between personality and second language learning behaviours. Moreover, the outcomes also show that introverts adopted more compensation strategies in learning English, whereas extroverts tend to use social strategies in the process of learning English as a second language (ESL). The findings will encourage educators to facilitate students in adopting appropriate learning strategies in order to achieve successful language learning.